Telemedicine for ENT: Quality of Care During the COVID-19 Pandemic at the Jose R. Reyes Memorial Medical Center in 2022 - Janella Mara Castro; Ryan Chua (Philippine Journal of Otolaryngology Head and Neck Surgery)
Objective: To assess the quality of care of telemedicine consultation during the COVID-19 pandemic at the Jose R. Reyes Memorial Medical Center in 2022 Methods: Design: Cross-Sectional Study Setting: Tertiary Government Training Hospital Participants: 210 patients